2017
DOI: 10.7717/peerj.3051
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional trait diversity of wild bees in different urban settings

Abstract: Urbanization is one of the major anthropogenic processes contributing to local habitat loss and extirpation of numerous species, including wild bees, the most widespread pollinators. Little is known about the mechanisms through which urbanization impacts wild bee communities, or the types of urban green spaces that best promote their conservation in cities. The main objective of this study was to describe and compare wild bee community diversity, structure, and dynamics in two Canadian cities, Montreal and Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 114 publications
(164 reference statements)
1
116
1
1
Order By: Relevance
“…Many researchers report that natural habitats display greater diversity of pollinators compared to urban areas (McIntyre and Hostetler 2001;Eremeeva and Sushchev 2005;Matteson et al 2008;Ahrné et al 2009). At the same time, data provided by other authors show that cities are important habitats for a considerable number of bee species (Saure 1996;Frankie et al 2005;Banaszak-Cibicka and Żmihorski 2012;Frankie et al 2013;Baldock et al 2015;Cariveau and Winfree 2015;Sirohi et al 2015;Threlfall et al 2015;Hall et al 2017;Normandin et al 2017), and urbanization has a lesser effect on bees than on other insects (Deguines et al 2012). For instance, urban parks in San Francisco, USA, support higher mean abundances of bumblebees (Bombus spp.)…”
Section: Discussionmentioning
confidence: 95%
“…Many researchers report that natural habitats display greater diversity of pollinators compared to urban areas (McIntyre and Hostetler 2001;Eremeeva and Sushchev 2005;Matteson et al 2008;Ahrné et al 2009). At the same time, data provided by other authors show that cities are important habitats for a considerable number of bee species (Saure 1996;Frankie et al 2005;Banaszak-Cibicka and Żmihorski 2012;Frankie et al 2013;Baldock et al 2015;Cariveau and Winfree 2015;Sirohi et al 2015;Threlfall et al 2015;Hall et al 2017;Normandin et al 2017), and urbanization has a lesser effect on bees than on other insects (Deguines et al 2012). For instance, urban parks in San Francisco, USA, support higher mean abundances of bumblebees (Bombus spp.)…”
Section: Discussionmentioning
confidence: 95%
“…, Normandin et al. ). With greater study, documenting the distribution of functional traits within a particular arthropod community can be used to predict the conservation value of focal habitats as well as potential desired insect‐mediated ecosystem services such as biological control, pollination, and nutrient cycling (Mulder and Vonk , Vonk et al.…”
Section: Introductionmentioning
confidence: 98%
“…frequent mowing, cutting down trees, replacing waste land, use of impervious materials) often changes green infrastructure and could, as a result, impoverish these habitats for urban flora and fauna (Pauleit & Breuste, 2011). Furthermore, it has to be taken into consideration that cities are a part of the larger landscape, and that urban areas are becoming increasingly important ecosystems, promoting the biodiversity of their surroundings (Goddard et al, 2010;Kowarik, 2011;Normandin et al, 2017;Werner & Kelcey, 2017). However, a recent study demonstrated that urban residents attached importance not only to the aesthetic character but also to the conservational aspects of urban green space (Southon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%